Organoleptic and Elongation Characteristics of Kiwi–Kepok Banana Fruit Leather with the Addition of Moringa Leaves - Habsari , Windi; Rahmah, Latifahtur; Hiranyo, Emanuella Adwitya Nanda (Jurnal Pangan Gizi dan Kesehatan, 2025)
Background: The growing demand for nutritious, practical snacks has driven innovation in fruit-based products such as fruit leather. Objectives: This study aims to evaluate the effect of Moringa oleifera leaf powder on the organoleptic and elongation characteristics of fruit leather made from kiwi and kepok banana. Methods: The research used a Completely Randomized Design (CRD) with five treatments based on different concentrations of moringa leaf powder (0–8 g). Organoleptic tests assessed aroma, color, taste, texture, and overall acceptability using a hedonic scale, while elongation was measured using a Texture Analyzer. Results: The result showed that increasing moringa content significantly improved aroma, color, and taste, but slightly decreased texture scores due to the fibrous nature of moringa. The highest overall acceptability was observed in the F4 formulation. Elongation results showed that moderate moringa addition (2–4 g) enhanced elasticity, with F1 (2 g) exhibiting the highest elongation (12.56%). Conclusions: These findings suggest that incorporating moringa at optimal levels can enhance the nutritional and sensory quality of kiwi–banana fruit leather without compromising its texture.